2021
DOI: 10.1186/s12882-021-02373-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between financial hardship and incident diabetic kidney disease in older US adults – a longitudinal study

Abstract: Background Financial hardship is associated with poor health, however the association of financial hardship and incident diabetic kidney disease (DKD) is unknown. This study aimed to examine the longitudinal relationship between financial hardship and incident DKD among older adults with diabetes. Methods Analyses were conducted in 2735 adults age 50 or older with diabetes and no DKD using four waves of data (2006–2012) from the Health and Retireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In addition, there was suggestive evidence that SNAP participation may mitigate the association of AL with moderate and severe food insecurity. Overall, these findings suggest that the link between food insecurity and an increased risk of chronic disease could be mediated by physiologic dysregulation and that appropriate intervention could help modify this association …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In addition, there was suggestive evidence that SNAP participation may mitigate the association of AL with moderate and severe food insecurity. Overall, these findings suggest that the link between food insecurity and an increased risk of chronic disease could be mediated by physiologic dysregulation and that appropriate intervention could help modify this association …”
Section: Discussionmentioning
confidence: 87%
“…Overall, these findings suggest that the link between food insecurity and an increased risk of chronic disease 3,4,6,[11][12][13][14][15] could be mediated by physiologic dysregulation 26 and that appropriate intervention could help modify this association. 26,42,45,46 A higher level of C-reactive protein, a validated biomarker of inflammation, in food-insecure individuals corroborates the evidence that food insecurity is associated with inflammation and related immune responses.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In analysis using data from the Health and Retirement Study, Black adults reported significantly more financial hardship than White adults (26). In a different analysis involving US adults with diabetes, NH Black adults showed a higher likelihood of financial hardship (27). Black adults were also more likely to experience financial hardship due to major life events, such as a global pandemic (28) and cancer treatment diagnosis (29).…”
Section: Introductionmentioning
confidence: 99%